FUNGSI JIWA KEHENDAK DALAM PSIKOLOGI PENDIDIKAN ISLAM - Imroatul Hasanah; Daris Salama Ulin Nuha; Titin Nurhidayati (As-Sulthan Journal of Education, 2026)
The will (al-irādah) is a fundamental element in Islamic educational psychology that functions as a driving force for behavior, learning motivation, and self-control among students. In the Islamic perspective, will is not merely understood as a psychological impulse, but as a spiritual potential integrated with reason and the heart in shaping human choices and moral responsibility. This study aims to analyze the function of the will in Islamic educational psychology and its relevance to students’ character formation. This research employs a qualitative descriptive method through library research by examining the Qur’an, Hadith, and relevant literature on psychology and Islamic education. The findings indicate that the will plays a strategic role in directing learning behavior, strengthening self-discipline, and fostering students’ moral and spiritual commitment. The development of the will in Islamic education can be implemented through the internalization of monotheistic values, habituation of worship practices, role modeling, and continuous moral education. Therefore, strengthening the will becomes a crucial foundation in realizing holistic Islamic education oriented toward the formation of faithful, ethical, and responsible individuals.